IEEE International Conference on Performance, Computing, and Communications, 2004
DOI: 10.1109/pccc.2004.1301209
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up and performance studies of three agent platforms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…A comparison study of four different Java-based multiagent platforms [26] shows that Jade provides the most efficient messaging service, whereas ZEUS [11] would be the worst one. Another comparative evaluation of three multiagent platforms [8], that again focuses on the messaging service, also concludes that Jade provides the best performance because it is built on Java RMI.…”
Section: Related Workmentioning
confidence: 95%
See 1 more Smart Citation
“…A comparison study of four different Java-based multiagent platforms [26] shows that Jade provides the most efficient messaging service, whereas ZEUS [11] would be the worst one. Another comparative evaluation of three multiagent platforms [8], that again focuses on the messaging service, also concludes that Jade provides the best performance because it is built on Java RMI.…”
Section: Related Workmentioning
confidence: 95%
“…During the last years, a lot of work has focused on testing the performance of existing multiagent platforms [1,8,9,12,20,24,26]. One of the main performance metrics considered has been the response time (i.e.…”
Section: Related Workmentioning
confidence: 99%
“…The Java Agent Development Framework (JADE) [ 24 ] agent platform is compliant with international Foundation for Intelligent Physical Agents (FIPA) [ 25 ] standards [ 26 , 27 ], and is thus used here as the foundation for building the IMAIS platform. In other words, the IMAIS agent environment, communication framework, and architecture are designed following the JADE specification.…”
Section: Requirement Analysis and System Designmentioning
confidence: 99%
“…Although JXTA is the most advanced P2P library currently available and is in general considered to be a good choice for implementing distributed computing platforms [46], performance studies have revealed weaknesses in the Java™ implementation of the version 2.0 protocol specification. That includes pipe latency and throughput for small messages [51], reliability of TCP connections [52], as well as rendezvous network stability [53] and convergence [54]. Apart from the fact that these shortcomings, which may be specific to the reference implementation, exist, the overall JXTA design is not optimized for P2P Grid Computing.…”
Section: Alternative Substrate Technologiesmentioning
confidence: 99%